The slippery slope - Snicket, Lemony (Egmont London, 2004)
In the perilous Mortmain Mountains, Klaus and Violet Baudelaire meet another well-read person, who helps them try to rescue Sunny from the villainous Count Olaf and his henchmen as they all near "the last safe place."